Enhancing Narrative and Visual Literacy of EFL Students through Bilingual Subtitled Historical Docudrama - Nicholaus Wayong Kabelen; Widya Adhariyanty Rahayu (Universitas Islam Negeri Palopo, 2026)
Many EFL learners experience difficulty understanding narrative structure and interpreting visual elements when exposed to authentic audiovisual materials. This study investigates the effect of bilingual-subtitled historical docudrama on students’ narrative and visual literacy. Using a quasi-experimental pretest–posttest control group design, 60 undergraduate EFL students (A2 level, CEFR) were divided into an experimental group (n=30) and a control group (n=30). The experimental group viewed a WR Soepratman historical docudrama with Indonesian–English subtitles, while the control group viewed the same video without subtitles. Results showed statistically significant improvements in both narrative and visual literacy in the experimental group compared to the control group (p < .001), with large effect sizes. The findings suggest that bilingual subtitles function as instructional scaffolding that supports dual literacy development. This study offers a novel contribution by integrating culturally grounded historical audiovisual media with bilingual subtitling to enhance narrative and visual literacy in EFL contexts.